Penyusunan Anggaran Per Unit Kerja Asosiatif Dengan Anggaran Berbasis Kinerja? - Andilo Tohom (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2015)
The process of preparing government agency budget can not be separated from the proposed work plan and budget of the division in government agencies based on its duties and functions. Each proposed activities, outputs and budget required then compiled into the budget of upper unit up to the level of Ministries/Agencies/Government. Nevertheless, it should be referred to objectives to be achieved by the government. A proper understanding of the principle of 'money follow function "is inherent in the notion of performance based budgeting should be owned by the parties involved in the budgeting process. Performance-based budgeting is governed by different provisions of the budget in our country, stressing the importance of the alignment of the activities/programs funded from the state budget with government targets. The literature study presented in this paper is aimed to provide important insight for government entities when preparing the budget.